Psychometric Properties of Indonesian Job-related Affective Well-being Scale: Examining Factor Structure Through CFA and ESEM - Silvia Kristanti Tri Febriana; Muhammad Abdan Shadiqi; Ahmad Helmi Nugraha; Meydisa Utami Tanau; Rusdi Rusli; Rahmiyati (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2026)
Job Affective Well-Being Scale (JAWS) is a psychological instrument used to measure emotional conditions in the context of work. However, research on the psychometric properties of JAWS in the Indonesian context remains limited. This study aims to test the construct validity of JAWS among 410 Indonesian workers (mean = 34.98; SD = 9.51) using a competing models strategy. This study compares three approaches: Confirmatory Factor Analysis (CFA), Exploratory Structural Equation Modelling (ESEM), and Set-ESEM. The results of the model comparison analysis indicated that the Modified 4-Factor Set-ESEM model was the best, balancing statistical accuracy and parsimony and accommodating natural cross-loadings among items within the same valence. The evaluation of measurement invariance across genders confirmed the instrument's stability at the configurational and metric levels, as well as partial scalar invariance. The final JAWS Indonesian version model with the Set-ESEM model shows that this instrument is valid, reliable, and fair in measuring affective well-being at work, and supports its use for research and organisational intervention purposes in Indonesia.